Effect of Empagliflozin on the Clinical Stability of Patients With Heart Failure and a Reduced Ejection Fraction: The EMPEROR-Reduced Trial. Issue 4 (26th January 2021) - Packer, Milton; Anker, Stefan D.; Butler, Javed; Filippatos, Gerasimos; Ferreira, João Pedro; Pocock, Stuart J.; Carson, Peter; Anand, Inder; Doehner, Wolfram; Haass, Markus; Komajda, Michel; Miller, Alan; et al.
Abstract : Background: Empagliflozin reduces the risk of cardiovascular death or hospitalization for heart failure in patients with heart failure and a reduced ejection fraction, with or without diabetes, but additional data are needed about the effect of the drug on inpatient and outpatient events that reflect worsening heart failure. Methods: We randomly assigned 3730 patients with class II to IV heart failure with an ejection fraction of ⩽40% to double-blind treatment with placebo or empagliflozin (10 mg once daily), in addition to recommended treatments for heart failure, for a median of 16 months. We prospectively collected information on inpatient and outpatient events reflecting worsening heart failure and prespecified their analysis in individual and composite end points. Results: Empagliflozin reduced the combined risk of death, hospitalization for heart failure or an emergent/urgent heart failure visit requiring intravenous treatment (415 versus 519 patients; empagliflozin versus placebo, respectively; hazard ratio [HR], 0.76; 95% CI, 0.67–0.87; P <0.0001). This benefit reached statistical significance at 12 days after randomization. Empagliflozin reduced the total number of heart failure hospitalizations that required intensive care (HR, 0.67; 95% CI, 0.50–0.90; P =0.008) and that required a vasopressor or positive inotropic drug or mechanical or surgical intervention (HR, 0.64; 95% CI, 0.47–0.87; P =0.005). As compared with placebo, fewer patients in the empagliflozin group reported intensification of diuretics (297 versus 414 [HR, 0.67; 95% CI, 0.56–0.78; P <0.0001]). Additionally, patients assigned to empagliflozin were 20% to 40% more likely to experience an improvement in New York Heart Association functional class and were 20% to 40% less likely to experience worsening of New York Heart Association functional class, with statistically significant effects that were apparent 28 days after randomization and maintained during long-term follow-up. The risk of any inpatient or outpatient worsening heart failure event in the placebo group was high (48.1 per 100 patient-years of follow-up), and it was reduced by empagliflozin (HR, 0.70; 95% CI, 0.63–0.78; P <0.0001). Conclusions: In patients with heart failure and a reduced ejection fraction, empagliflozin reduced the risk and total number of inpatient and outpatient worsening heart failure events, with benefits seen early after initiation of treatment and sustained for the duration of double-blind therapy. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03057977. Abstract : Supplemental Digital Content is available in the text.